CD8+ T cells are activated in an antigen-independent manner in HIV-infected individuals - Bastidas, Sonia; Graw, Frederik; Smith, Miranda Z.; Kuster, Herbert; Guenthard, Huldrych F.; Oxenius, Annette (Journal of Immunology, 2014)
Hyperactivation of T cells, particularly of CD8+ T cells, is a hallmark of chronic HIV 1 (HIV-1) infection. Little is known about the antigenic specificities and the mechanisms by which HIV-1 causes activation of CD8 + T cells during chronic infection. We report that CD8+ T cells were activated during in vivo HIV-1 replication irrespective of their Ag specificity. Cytokines present during untreated HIV-1 infection, most prominently IL-15, triggered proliferation and expression of activation markers in CD8+ T cells, but not CD4+ T cells, in the absence of TCR stimulation. Moreover, LPS or HIV-1-activated dendritic cells (DCs) stimulated CD8+ T cells in an IL-15-dependent but Ag-independent manner, and IL-15 expression was highly increased in DCs isolated from viremic HIV-1 patients, suggesting that CD8+ T cells are activated by inflammatory cytokines in untreated HIV-1 patients independent of Ag specificity. This finding contrasts with CD4+ T cells whose in vivo activation seems biased toward specificities for persistent Ags. These observations explain the higher abundance of activated CD8+ T cells compared with CD4+ T cells in untreated HIV-1 infection. Copyright © 2014 by The American Association of Immunologists, Inc.
CRIS-Team Scopus Importer:2022-12-14